Motivation for Open Collaboration: Crowd and Community Models and the Case of OpenStreetMap. (May 2013) - Budhathoki, Nama R.; Haythornthwaite, Caroline
This article presents an examination of motivational factors relating to contribution to the wiki OpenStreetMap, a site for voluntary geographic information. Based on a wide literature review of motivation, open source, volunteerism, and serious leisure, a questionnaire was created and completed by 444 OpenStreetMap contributors. Results of judgments of the motivational importance of 39 reasons for contribution are presented and considered in relation to models of contributory behavior for crowd- and community-based online collaborations. Positive and important motivators were found that accorded with ideas of the "personal but shared need" associated with contribution to open-source projects, co-orientation to open-source and geographic knowledge, and attention to participation in and by the community. Differences in motivation between serious and casual mappers showed that serious mappers were more oriented to community, learning, local knowledge, and career motivations (although the latter motivation is low in general), and casual mappers were more oriented to general principles of free availability of mapping data.